ANALISIS FAKTOR RESIKO KEJADIAN STUNTING PADA ANAK USIA 12–59 BULAN DI PROVINSI NUSA TENGGARA BARAT - Novia Dewi Anggraini (UNUSA Press, 2019)
Stunting among children under five can giving bad impact for chidren because it make less optimum of brain development. In 2017, there was 37,2% children under five years West Nusa Tenggara Province experience stunting.This study aimed to assess risk factor of stunting among children under five years in West Nusa Tenggara Province.This study was secondary data analysis from Indonesian Family Life Survey wave 5 (IFLS-5) in 2014-2015. Samples of this research were children age 12-59 months in West Nusa Tenggara Province. The number of the samples was 456 children. The relationship between variables were analyzed by chi-square test and the relative risk were analyzed by logistic regression. Result show that risk factor of stunting among children age 12-59 months in West Nusa Tenggara Province were weight of birth less than 2500 gram (p=0,001; OR = 3,303; 95% CI = 1,6-6,816), anemia of children (p=0,001; OR = 2,199; 95% CI = 1,469-3,291), age of mother at birth less than 18 years old (p=0,001; OR = 6,867; 95% CI = 1,481-31,834), age of mother at birth more or same with 35 years old (p=0,001 ; OR=0,515; 95% CI = 0,282 – 0,937), and education level of mother (p=0,6511; OR: 0,651; 95% CI = 0,439-0,966). The conclusion that the risk factor of stunting among children age 12-59 months in West Nusa Tenggara Province were weight of birth, anemia, age of mother at birth, and education level of mother. Keywords: stunting, risk factor, toddler